PERLINDUNGAN HUKUM MOTIF KAIN TENUN IKAT DAYAK KABUPATEN SINTANG MENURUT UNDANG - UNDANG NOMOR 28 TAHUN 2014 TENTANG HAK CIPTA - Victor Emanuel (Universitas Kapuas Sintang, 2022)
The motif of Dayak ikat cloth in Sintang Regency is a communal intellectual right belonging to the Dayak community of Sintang Regency which is a hereditary heritage which is regulated in Law Number 28 of 2014 concerning Copyright. As an intellectual right, Dayak Ikat Woven Fabrics in Sintang Regency are one of 33 Types of Ikat Weaving in Indonesia, and a form of protection that is carried out through data collection on communal rights at the Ministry of Law and Human Rights of the Republic of Indonesia. We did this research using normative juridical research. The results of the study show that the legal protection of the communal intellectual rights of Dayak ikat weaving in Sintang district is only limited to data collection by the Ministry of Education, Culture, Research and higher education, UNESCO.If there is plagiarism of motifs by outside parties (third parties) on the motifs of Dayak ikat cloth in Sintang Regency on modern textile products that are commercial or economic in nature, there is no form of legal protection. Therefore, there needs to bea way out from the Sintang Regency Regional government in the form of a permit by plagiarists or those who imitate the motif, and a kind of compensation or form of royalty to the Sintang Regency Dayak Ikat weavers who are members of their community.Keywords: Legal protection, motives, communal intellectual rights